INSTITUTIONAL PREREQUISITES OF MODERNIZATION OF KAZAKHSTAN ECONOMY - R. B. Gabdullin (Russian Journal of Economics and Law)
Objective: determining and grounding the conditions and prerequisites of institutional modernization of economy in the context of forming the industrial-innovative model of development of Kazakhstan Republic. Method: abstract-logical. Results: basing on the analysis of economic processes under various conditions of market environment, the necessity is revealed to increase the institutional constituent of modernization of Kazakhstan national economy. Scientific novelty: theoretical interpretation of innovative industrialization processes taking place in the national economy from the point of view of correspondence to institutional conditions . Practical value: basing on research of theoretical basis of institutional transformations, practical recommendations are given, promoting achieving the high results with additional synergetic effect at all levels of economy.